Determinants of Technical Efficiency of Wheat Producers of Kailali District, Nepal (SAARC Journal of Agriculture, 2025)
Wheat is one of the major staple crops of Nepal, so it is inevitable to increase its productivity for sustainable food supply. The national average wheat productivity is quite below compared to neighboring countries. Therefore, this study envisages measuring technical efficiency of wheat farmers to understand its determinants, using randomly selected household data from 101 wheat farmers of Dhangadhi Sub Metropolitan city. Results showed that average technical efficiency is 90% and hence there is a chance to increase wheat production by up to 10% through appropriate crop management practices. All the inputs variables viz. land, labor and capital, had positive and significant relation with the production model and hence were vital for increasing productivity and income of wheat growers. The technical inefficiency model showed that age, education, and experience of household heads had a significant role. The most striking finding of this research was the role of seed replacement, which was found to have significant positive relations that increased the technical efficiency of the wheat growing farmers. This shows that farmers who replaced seed frequently (after every 1-5 years) had a high probability of increasing the efficiency in wheat production. However, availability of quality seeds at an affordable price is of the utmost concern. Government research institutions need to focus on increasing outreach of quality seeds and extension institutes need to focus on creating awareness of the farmers about the importance of seed replacement.SAARC J. Agric., 23(1): 25-39 (2025)